Effect of genotype, concentration and timing of salicylic acid application to Phalaenopsis against Dickeya dadantii infection - I Putu Wahyu Sanjaya; Dewi Sukma; Sudarsono Sudarsono; Ming-Tsair Chan (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Sanjaya IPW, Sukma D, Sudarsono, Chan MT. 2020. Effect of genotype, concentration and timing of salicylic acid application to Phalaenopsis against Dickeya dadantii infection. Biodiversitas 21: 4317-4323. Soft-rot because of Dickeya dadantii (Dd) infection is one of the most difficult to control, affecting the cultivation of Phalaenopsis in tropical regions. Salicylic acid (SA) is known as an inducer of resistance against pathogens in some plant species. The study aim to identify the effects of genotypes, concentrations, and timing of salicylic acid application to Phalaenopsis against D. dadantii inoculation. In experiment 1, eight Phalaenopsis genotypes were treated by SA at doses of 0 and 60 ppm and then inoculated with D. dadantii. At a dose of 60 ppm, SA did not increase the resistance to D. dadantii in any genotypes. In experiment 2, a representative of a very susceptible genotype (P. amabilis) was treated with high SA concentrations (60, 360, and 720 ppm). The results demonstrated that at SA concentrations of 360 and 720 ppm, slightly increase P. amabilis resistance to D. dadantii. In experiment 3, the most effective SA concentration (720 ppm) was used at 2, 3, 5, or 7 days after SA treatment. The timing of the SA application did not affect the resistance of P. amabilis to D. dadantii. The present study shows that SA concentrations up to 60 ppm did not inhibit D. dadantii infection. Nevertheless, such inhibition was observed at a high SA dose (720 ppm) for a short period.